Coinfection with Viral Hepatitis in HIV patients in 2023 - Barreiro, Pablo; Moreno-Torres, Víctor; Soriano, Vicente (AIDS reviews, 2023)
According to UNAIDS roughly 1.5 million new HIV infections occur each year worldwide. The number of persons living with HIV (PLWH) is estimated around 38 million globally, of whom 25 million live in Sub-Saharan Africa.
Keywords: viral hepatitis; coinfection; HIV; Scopus; JCR